KETEGUHAN REKAT RESORSINOL FORMALDEHIDA PADA KAYU YANG DIA WETKAN DENGAN CELCURE - Jamal Balfas (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
Production of laminated structural timbers suitable for use under severe conditions dates back to the development of resorcinol and phenol-resorcinol adhesives. These adhesives could provide highly durable bonds with untreated wood. Because preservative treatment of the - wood is commonly required, it became necessary to investigate the effect of the treatment on glue bond strength.This study examined the shear strength of resorcinol formaldehyde on the untreated and cetcure treated timbers. Additionally, a mechanical and a chemical surface activation treat- ments were imposed lo the system prior lo gluing. Species included for the study were: jeungjing (Paraserianthes falcataria (L.) Nielsen, adinandra (Adinandra brasii Kobuski) and pala burung (Horsfieldia sylvestris Warrb.). Defect-free airdried wood slicks measuring 50 mm (radial) x 50 mm (tangential) x 500 mm (longitudinal) were divided into two groups, of which one group was celcure-treated using an empty-cell process and the other was remained as control. Each slick was then cut into billets for adhesive lamination. Surface activation treatments were made mechanically by sanding wood surface with an 80-grit abrasive paper, or chemically by smearing wood surface with IM solution of NaOH approximately 24 h before gluing. Resorcinol formaldehyde was applied to each surface at a spread rate of 120 mg/cm2. Panels were clamped at 12 kg/cm2 for 7 h as recommended by the adhesive manufacturer. Each panel was cut into four shear specimens, of which two specimens were tested in dry condition and the remaining after 24 h immersion in water at room temperature. Strength loss due to wetting was also determined.Results showed that bond strength of resorcinol formaldehyde varied according to wood species. Jeungjing had a weaker bond strength than adinandra and pala burung. Preservative treatment had no deteriorating effects on dry shear strength, but it did reduce the wet shear strength of wood laminates. The application of surface activation treatments was more effective on the higher extractive contained species (adinandra and pala burung) and the unpreserved laminates. Surface mechanical treatment showed a better improvement on bond strength than the chemical treatment. Jeungjing experienced a higher strength loss during immersion than